On fund mapping regressions applied to segregated funds hedging under regime-switching dynamics - Denis-Alexandre Trottier; Frédéric Godin; Emmanuel Hamel (Risks, 2018)
Insurers issuing segregated fund policies apply dynamic hedging to mitigate risks related to guarantees embedded in such policies. A typical industry practice consists of using fund mapping regressions to represent basis risk stemming from the imperfect correlation between the underlying fund and its corresponding hedging instruments. The current work discusses the implications of using fund mapping regressions when the joint dynamics of the underlying and hedging assets is a regime-switching process. The potential underestimation of capital requirements stemming from the use of a fund mapping regression under such dynamics is discussed. The magnitude of the latter phenomenon is quantified through simulations calibrated on market data.
Keywords: 330; basis risk; hedging; segregated funds; variable annuities; risk measures; risk management; regime-switching